Consequences of Lethal-Whole-Body Gamma Radiation and Possible Ameliorative Role of Melatonin - Ehsan Mihandoost; Alireza Shirazi; Seied Rabie Mahdavi; Akbar Aliasgharzadeh (The Scientific World Journal)
Gamma radiation induces the generation of free radicals, leading to serious cellular damages in biological systems. Radioprotectors act as prophylactic agents that are administered to shield normal cells and tissues from the deleterious effects of radiation. Melatonin synergistically acts as an immune-stimulator and antioxidant. We investigated the possible radioprotective role of melatonin (100 mg/kg i.p.) against lethal-whole-body radiation- (10 Gy) induced sickness, body weight loss, and mortality in rats. Results of the present study suggest that exposure to lethal-whole-body radiation incurred mortality, body weight loss, and apoptosis and it also depleted the immunity and the antioxidant status of the rats. Our results show that melatonin pretreatment provides protection against radiation induced mortality, oxidative stress, and immune-suppression. The melatonin pretreated irradiated rats showed less change in body weight as compared to radiation only group. On the other hand, melatonin appeared to have another radioprotective role, suggesting that melatonin may reduce apoptosis through a caspase-3-mediated pathway by blocking caspase-3 activity.